Mobile Money Enriches the Financial Literacy in Developing Economies: Quantitative Evidence from Small Businesses in Africa Post-COVID-19 - Chowdhury, Dababrata; Koroye, Ebimoboere; Ayertey, Samuel; Nyame, Derick; Garrick, John; Moussa, Nahla (International Journal of Interactive Mobile Technologies (iJIM), 2026)
This study examines the potential of mobile money (MM) to enhance the financial literacy (FL) of small and medium enterprises (SMEs) owners in Africa. Following the pandemic, regional policy interventions have promoted MM; however, its maximum potential remains untapped due to systemic impediments. Although modest increases have been observed in the level of financial inclusion and financial capacity building, developing economies like Nigeria remain far from achieving significant progress toward digital financial integration. The Actor-Network Theory (ANT) is adopted as a conceptual lens to address the interaction between users and regulators as “Actors” on one side and MM as an “Actant” on the other side. The paper develops a behavioural model that presents four stages of “actors-actant” interaction, including “problematisation”, “interessment”, “enrolment”, and “mobilisation”. Evidence is drawn from a mixed-methods approach, comprising 250 survey respondents and 10 interviews with regulators. Quantitative data were analysed using SPSS, while interviews were analysed based on thematic coding. Findings indicate a high level of awareness and widespread adoption of MM among the population. However, it exhibits a stark urban-rural divide: fund transfers are found overwhelmingly concentrated in urban centres, with only 3.3% of such transfers reaching rural areas. Mobilisation, knowledge of MM, and rate of adoption do not have a significant impact on FL in this developing context. Top-down adoption and governmental intervention appear to play a significant role in the accelerating rate of financial literacy.